Morbidity profile of the patients attending the health camp in Ramanagar district, Karnataka - Patil, Savita S.; Seeri, Jayashree S.; D. M., Narayana Swamy (International Journal Of Community Medicine And Public Health, 2019)
Background: Free health camp is an important means to cater health services to the needy people in an underdeveloped county like India with difficult geographical terrain. The objective of this study was to assess the morbidities of patients attending the free health camp in Ramanagara District, Karnataka. Methods: A cross sectional descriptive study was conducted at free health camp in Jogaradoddi, Ramanagara District, Karnataka, by the staff and interns of department of community medicine of a medical college. All the individuals who attended the camp were included in the study. Patients who attended the health checkup camp were assessed for morbidity. Data collected by semi structured questionnaire was entered into Microsoft Excel and analyzed using SPSS version-17.0. Results: A total of 123 patients visited the health camp, among them 68(55.28%) of them were males and 55 (44.71%) were females. 41 (33.8%) were in the age group of 21-30 years. Majority were skilled workers with 30(26.1%), 18 (15.7%) were unemployed and only 1 (0.9%) were professionals .About 47 (46.1%) had normal body mass index, 26 (25.5%) were overweight, 10 (9.8%) were obese and 19 (18.6%) were underweight. It was observed that diseases with musculoskeletal system and gastrointestinal system were reported among 35 (28.5%) and 20 (16.3%) of the attendees respectively, 9 (7.7%) individuals presented with hypertension, 6 (5.5%) with diabetes mellitus. Conclusions: The study helped identify the common diseases in the selected area, improve the health, provide counselling and create awareness at the community level.